Pengaruh Green Product dan Green Price Terhadap Purchase Intention pada Produk Wateru Bamboo Tissue di Kota Malang - Putri Marcela; Arni Utamaningsih; Farida Akbarina (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The use of paper tissues in daily life has become a habit of people in Indonesia, especially in urban areas. Excessive use of tissues causes problems for the environment. Consumers who are concerned about environmental issues are more interested in environmentally friendly products that are not only quality, but also have a positive impact on the environment. Green Product is a product that is not harmful to humans and the environment, does not produce excessive waste, Green Price is a nominal value of the exchange rate set by balancing the price with product quality that considers environmental impacts and products that have added value. This study aims to analyze the effect of Green Product and Green Price on Purchase Intention of wateru Bamboo Tissue Products. This research is quantitative research. The data collection method uses a questionnaire distributed online to 100 respondents who know Wateru Bamboo Tissue products in Malang City. The sampling used purposive sampling technique. Data analysis in this study used multiple linear regression analysis and hypothesis testing. The classic assumption test results show that the data has met the criteria. The coefficient of determination test results are 0.484 or 48.3% and the rest is influenced by other variables. The results of the Green Product and Green Price hypothesis test partially and simultaneously have a significant effect on Purchase Intention on Wateru Bamboo Tissue products in Malang City. Based on the results of this study, it can be concluded that Wateru Bamboo Tissue products are advised to continue to develop Green Products and clarify the reasons for Green Price products in order to increase Purchase Intention on their products.